2015
DOI: 10.3349/ymj.2015.56.4.981
|View full text |Cite
|
Sign up to set email alerts
|

Modified Peritoneal Dialysis Catheter Insertion: Comparison with a Conventional Method

Abstract: PurposeThe conventional trocar and cannula method in peritoneal dialysis (PD) catheter insertion has its limitation in clinical setting. The aim of this study was to compare a modified method for percutaneous PD catheter insertion with the conventional method, and demonstrate advantages of the modified method.Materials and MethodsPatients at a single center who had percutaneous PD catheters inserted by nephrologists from January 2006 until September 2012, using either a modified method (group M) or the convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…Lee et al reported [29] that 102 patients who received PD were divided into two groups, which received either laparoscopic or conventional catheter placement, and were followed up for 6 months after the operation. The results showed that the probability of transabdominal tube displacement and blockage in patients who received traditional laparotomy was 12%.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported [29] that 102 patients who received PD were divided into two groups, which received either laparoscopic or conventional catheter placement, and were followed up for 6 months after the operation. The results showed that the probability of transabdominal tube displacement and blockage in patients who received traditional laparotomy was 12%.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with laparoscopic minimally invasive PD catheterization, conventional PD catheterization has the following disadvantages: 1) a long operation time, strong pain, a long incision length and a slow recovery [30] ; 2) a limited field of vision, as it is not as open as the laparoscopic minimally 11 invasive operation, and blindcatheter placement by hand leads to inaccurate catheter placement, easy catheter movement or catheter obstruction by the greater omentum [3] ; 3) the incision infection rate is high, with ESRD often associated with a variety of diseases, poor resistance, and traditional PD catheterization associated with a longer incision length and a high staining rate that often lead to surgical failure [3] ; and 4) the operation is more difficult for obese patients [3] . Zhang Lee et al reported [32] that 102 patients who received PD were divided into two groups, which received either laparoscopic or conventional catheter placement, and were followed up for 6 months after the operation. The results showed that the probability of transabdominal tube displacement and blockage in patients who received traditional laparotomy was 12%.…”
Section: Discussionmentioning
confidence: 99%
“…Se introduce el catéter a través de la férula, dirigiendo la punta hacia hueco pélvico por la corredera izquierda, siempre respetando la memoria del catéter. La pelvis izquierda es preferida ya que las asas intestinales -con su peristalsis-tienden a perpetuar el catéter en su lugar [10] (figura 3). Una vez introducido el catéter hasta el dispositivo proximal de dacron, se abre la férula para extraerla.…”
Section: Figura 1 Se Marcan Los Bordes De Los Rectos Abdominales Y Lunclassified
“…Al parecer, con la misma eficacia [8] y no mayores complicaciones [9] que la colocación quirúrgica. Las principales ventajas que presenta esta técnica son la economía y el tiempo de hospitalización, así como el uso de anestesia local y sedación durante su colocación, evitando las complicaciones potenciales de la anestesia general [10].…”
Section: Introductionunclassified